Sequencing and phylogenetic analyses of talaromyces amestolkiae from amazon: A producer of natural colorants - Zaccarim, Bruna R. [UNESP]; de Oliveira, Fernanda [UNESP]; Passarini, Michel R. Z.; Duarte, Alysson W. F.; Sette, Lara D. [UNESP]; Jozala, Angela F.; Teixeira, Maria F. S.; de Carvalho Santos-Ebinuma, Valéria [UNESP] (Wiley, 2019)
The population interest in health products is increasing day-by-day. Thus, the demand for natural products to be added in food and pharmaceutical commodity is also rising. Among these additives, colorants, which provides color to products, can be produced by microorganism through bioprocess. Looking for new source of natural colorants, fungi have been employed to this purpose producing novel and safer natural colorants. So, the main goal of this study was to describe a Talaromyces species able to produce natural colorants and investigate nutritional parameters of colorants production using statistical tool. The taxonomy classified the microorganism as Talaromyces amestolkiae. The statistical design evaluated pH and glucose, meat extract and meat peptone concentration as independent variables, and red colorants production as main response. Under the best condition (g/L: glucose 30, meat extract 1, meat peptone 10, and initial pH of 7.0) an increase of 229% in the red colorant production was achieved as compared with the initial media used. The dried fermented broth containing red colorants showed low cytotoxicity against fibroblasts cells (IC 50 > 187.5 g/L) and effective antimicrobial activity against S. aureus (MIC of 2.5 g/L). Thus, T. amestolkiae colorants can be attractive to food and pharmaceutical applications as it does not produce toxic compounds and can promote protection against microorganism contaminants. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 35: e2684, 2019.
Keywords: antimicrobial activity; bioprocess; natural colorants; statistical tool; Talaromyces